MCQs in Biochemistry - Lal, Harbans; Pandey, Rajesh (New Delhi : Cbs Pub. & Distribu, Pvt. Ltd., 2013)
The present compilation, in the subject of Biochemistry, endeavors us to help students preparing for the All India PG Medical Entrance Examination. It includes questions from all categories, i.e. from the simplest ones to real brain teasers, in order to cater the needs of the unprepared students who start studying at the eleventh hour, besides, of course, the committed ones who are well conversant with the subject.
pharmacy bookfair2015
Includes Bibliography.
Electronic reproduction.
Keywords: Biochemistry -- Examinations, questions, etc; Electronic books